Talking about nothing truth with or without objects - Azzouni, Jody. (New York ; Oxford : Oxford University Press, 2010)
This work reconfigures metaphysics in radical ways that allow the accommodation of our ordinary ways of speaking of what does not exist while retaining the absolutely crucial presupposition that such objects exist in no way at all, have no properties and are not the truth-makers for the truths and falsities that are about them.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Ontology